2015
DOI: 10.1080/13504509.2015.1111268
|View full text |Cite
|
Sign up to set email alerts
|

The potential of current legal structures to support Aboriginal and Torres Strait Islander interests in the Australian bush food industry

Abstract: There are complex connections between Australia's native plants and first peoples, the Aboriginal and Torres Strait Islander peoples. The maintenance of these connections is central to Aboriginal and Torres Strait Islander culture and well-being and the tangible realisation of Australian policy commitments. Diverse cultural connections combine with other motivations to underpin an array of Aboriginal and Torres Strait Islander interests in the commercial development of traditional plant foods ('bush foods'). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This reproduces and enforces Whiteness in similar ways to the use of new technologies. A recent study showed that Indigenous people control and run just 1% of the entire Bush Food industry (Mitchell and Becker, 2019) with access and ownership of land playing a significant factor (Lingard, 2016).…”
Section: Whiteness and (Nano) White Food: Impacts For Indigenous Health And Relationships To Foodmentioning
confidence: 99%
“…This reproduces and enforces Whiteness in similar ways to the use of new technologies. A recent study showed that Indigenous people control and run just 1% of the entire Bush Food industry (Mitchell and Becker, 2019) with access and ownership of land playing a significant factor (Lingard, 2016).…”
Section: Whiteness and (Nano) White Food: Impacts For Indigenous Health And Relationships To Foodmentioning
confidence: 99%
“…Sherman (, p. 304) states that this concern also applies where Australian plants have already been collected and land owners not compensated by third parties. Further, Aboriginal and Torres Strait Islander peoples own or control access to around 25–30% of Australian land (Lingard, , p. 177). Traditional knowledge from areas outside of this control is not protected through these regulations.…”
Section: Current Australian Protectionmentioning
confidence: 99%
“…Indigenous Australians’ knowledge natural resources and their traditional uses is extensive, and has large potential to be harnessed in the development of future inventions. Further, Aboriginal and Torres Strait Islander peoples own or control access to around 25–30% of Australian land (Lingard, , p. 177). Australia has a well‐established system of commercial and intellectual property (IP) law, and a strong scientific and research sector (Understanding the NCA, , p. 4).…”
Section: Introductionmentioning
confidence: 99%